Not enough by half: NFAT5 haploinsufficiency in two patients with Epstein-Barr virus susceptibility - Lopez-Rivera, Daniela Olivia; Castano-Jaramillo, Lina Maria; Yamazaki-Nakashimada, Marco Antonio; Ramirez Uribe, Rosa María Nideshda; Corcuera Delgado, Celso Tomás; Ignorosa-Arellano, Karen R.; Medina-Torres, Edgar Alejandro; Berrón Ruiz, Laura; Espinosa-Padilla, Sara Elva; Scheffler-Mendoza, Selma C.; López-Velázquez, Gabriel; Cruz-Munoz, Mario Ernesto; et al. (Frontiers in Immunology, 2022)
INTRODUCTION: The transcription factor Nuclear factor of activated T cells 5 (NFAT5), pivotal in immune regulation and function, can be induced by osmotic stress and tonicity-independent signals. OBJECTIVE: We aimed to investigate and characterize two unrelated patients with Epstein-Barr virus susceptibility and no known genetic etiology. METHODS: After informed consent, we reviewed their electronic charts, extracted genomic DNA, performed whole-exome sequencing, filtered, and prioritized their variants, and confirmed through Sanger sequencing, family segregation analysis and functional assays, including lymphoproliferation, cytotoxicity and natural killer cells characterization. RESULTS: We describe 2 cases of pediatric Mexican patients with rare heterozygous missense variants in NFAT5 and EBV susceptibility, a school age girl with chronic-active infection of liver and bowel, and a teen age boy who died of hemophagocytic lymphohistiocytosis. DISCUSSION: NFAT5 is an important regulator of the immune response. Haploinsufficiency has been described as an immunodeficiency syndrome affecting both innate and adaptive immunity. EBV susceptibility might be another manifestation in the spectrum of this disease.